Cervical cancer screening and prevention: how aware is the Indian woman? - Saxena, Trapti M.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Carcinoma of the cervix is the second most common cancer in women worldwide. It is the commonest cancer among Indian women. Awareness regarding cervical cancer and its prevention is quite low amongst Indian women. The Pap test is a simple and cost-effective technique for early diagnosis of cervical cancer. Methods: It was a cross sectional study conducted in the months of September and October 2018. We included 200 women between 30 and 60 years of age. Results: In present study, out of 200 respondents, 160 (80%) respondents got married after 21 years of age while 40 (20%) respondents got married below 21 years of age. 148 (74%) respondents had 2 children, 30 (15%) respondents had one child while 22 (11%) respondents had 3 children. 166 (83%) had heard about cervical cancer, 24 (12%) knew that cervical cancer can be cured if detected in early stage while only 10 (5%) knew that it can be prevented. 54 (27%) respondents knew that pap smear test should be done as screening test to detect cervical cancer in early stage while 22 (11%) respondents knew about HPV vaccine as preventive measure. Conclusions: In present study, though women have heard about cervical cancer, proper knowledge was very less. Also, awareness about HPV vaccine and Pap smear was less. There is need for proper information and facilities for pap smear and HPV vaccination.